A decision support tool for energy efficient synchromodal supply chains. (10th June 2018) - Farahani, Nasibeh Zanjirani; Noble, James S.; Klein, Cerry M.; Enayati, Moein
Abstract: The industrial supply chain is a significant consumer of limited energy resources worldwide. Companies have been encouraged to reduce energy costs by restructuring their logistics network, improving their transportation asset fuel efficiency, and reducing travel distance. The recent evolution of synchromodal supply chains has focused on flexible transportation modes as a new option for supply chain managers to reduce the total energy cost. Illustrating the monetary advantages of such reconfigurations will guide decision makers to get the most from all available options. In this paper, the process of modeling and developing a user-friendly, customizable tool for supply chain decision makers called the Synchromodal Supply Chain Energy Analysis tool (SySCEA) is presented. SySCEA enables the analysis of the overall environmental and economic effects due to supply chain fuel consumption and changing network configuration as it relates to order quantity, demand quantity, product size, packaging, mode and transportation assets. Currently, SySCEA supports up to five arc/routes, plus the first and last mile, for a synchromodal supply chain. However, due to the modular nature of the tool it is simple to extend it to larger networks. Highlights: Mathematical model for supply chain energy usage calculation, applied in a user-friendly tool. Synchromodal transportation model to select the best mode and transportation asset based on energy usage. Model considers effects of customer orders, first/last mile transportation and variations in packaging type on energy usage.